The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/7596069
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Dynamics of Urogenital Schistosomiasis in the Rural Community of Ebonyi State, South Eastern Nigeria

Abstract: This study accessed the dynamics of urogenital schistosomiasis transmission in Nkalagu Community. A total of 500 mid-day urine samples were collected and transported to Microbiology Laboratory, Ebonyi State University, for analysis. 10ml each of the urine samples was centrifuged at 2500 rpm for 5 minutes. Transmission potential of snail intermediate host of Schistosomes collected from different sampling station at the transmission sites within the study community was equally accessed. The snail species collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
5
9
0
Order By: Relevance
“…[25] It has been reported that the frequency of water contact activities such as swimming to increase the risk of transmitting or acquiring the infection in endemic settings. [26][27][28] Acceptability and uptake of praziquantel among primary school children are crucial for the control of urogenital schistosomiasis and for the prevention of long-term morbidity. [29] The study ndings revealed a statistically signi cant association between the uptake of the praziquantel and the prevalence of urogenital schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…[25] It has been reported that the frequency of water contact activities such as swimming to increase the risk of transmitting or acquiring the infection in endemic settings. [26][27][28] Acceptability and uptake of praziquantel among primary school children are crucial for the control of urogenital schistosomiasis and for the prevention of long-term morbidity. [29] The study ndings revealed a statistically signi cant association between the uptake of the praziquantel and the prevalence of urogenital schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, from statistical analysis, it is reasonable to suggest that the active age group (11-24 years) may fall more into the secondary education category. In Nigeria, the age group 11-20 years was the most active age group frequently engaging in activities that bring them in contact with infested water bodies [46]. The sex dependent pattern of schistosome infections is widely reported [43].…”
Section: Contrary To Findings In Munyenge Mount Cameroonmentioning
confidence: 99%
“…Acceptability and uptake of praziquantel among primary school children are crucial for the control of urogenital schistosomiasis and the prevention of long-term morbidity [29]. The study findings revealed a statistically significant association between the uptake of the praziquantel and the prevalence of urogenital schistosomiasis.…”
Section: Discussionmentioning
confidence: 81%